Respostas
respondido por:
4
Explicação passo-a-passo:
a) 3²+3 / 2•3-1 = 9+3 / 6-1 = 12/5 = 2,4
b) 2²-2•1 / 2•2+1 = 4-2 / 5 = 2/5 = 0,4
c) - (-1)²+(-1)+1 / - 2(-1)²-(-1)+3 = - 1-1+1 / - 2+1+3 = -1/2 = - 0,5
d) 0,3+3 / 0,3+0,7 = 3,3/1 = 3,3
aamandinha316ozqca3:
obrigadaaaa
respondido por:
4
Explicação passo-a-passo:
a) Colocando 3 no lugar de x:
b) Colocando 2 no lugar de p e 1 no lugar de q:
c) Colocando -1 no lugar de x:
d) Colocando 0,3 no lugar de a:
Perguntas similares
5 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás